The effect of galaxy components in the lopsisdedness of galaxies - Kaur, Navinder (My University, 2019)
This thesis is an account of effect of components of the galaxies on the lopsidedness seen at the centers of the galaxies. First we discuss about galaxies and their types. We give an account of some basic terminology used in the thesis and then we discuss about Milky Way galaxy and its components. A brief account of the observations (lopsided stellar distribution and off-centered dark matter halo) at the center of the galaxies is also given. The stellar orbits are found to follow epicyclic orbits, which we also discuss in this thesis. The implications of off-centered dark matter halo on the orbits of stars is the deviation from circular orbits. The effect of dark matter halo is the off-centered distribution of the stars at the center of the galaxies. This model was first proposed by Prasad and Jog (2017), however their analysis does not have the central black hole in their galaxy model. We explicitly add the black hole in he disk and follow their calculations to give the orbits of the stars. The effect of presence of black hole can be seen in the radial and azimuthal velocities of the stars.
Keywords: Mathematical modeling; Galaxies; Dark matter halo; Stellar orbits